[Roberto Mendoza lectures on the socio-emotional changes of an adolescent] - Mendoza, Roberto (Animo Repository, 1998)
Roberto Mendoza of the Psychology Department lectured before first year high school students of La Salle Green Hills (LSGH) on the socio-emotional changes of an adolescent as he discovers his sexual self in a forum also attended by the religious, medical, and the parent sectors.